Turbidity removal by rapid sand filter using anthracite coal as capping media - Tamakhu, Gopal; Amatya, Iswar Man (Journal of Innovations in Engineering Education, 2021)
Rapid sand filters are very common in all conventional water treatment plants. Capping of existing rapid sand filters can be the promising method of improving the performance of rapid sand filters. Capping is process in which upper sand bed layer of few cm is replaced with capping material. However, this technique is limited in India due to unavailability of filter materials apart from sand. Some materials suitable for capping are anthracite coal, PVC granules, bituminous coal, broken bricks, etc. The attempt is made to study the effect of capping of Rapid sand filters by the use of anthracite coal as a capping media by pilot scale study. A series of test runs and experiments using different influent turbidity were tried. The pilot scale study has shown very encouraging results. Comparative analysis shows that higher rate of filtration is possible along with higher filter run and less backwash requirement. In the present work, conventional rapid sand filter and capped rapid sand filter are compared.